Contrastive Analysis of Paremiologically Units on The Basis of Professional Lexicon in English and Uzbek Languages - Khamzayev Otakhon Erkinovich (Genius Journals, 2023)
This article analysis of proverb and aphorism are considered as paremiological units, and paremiological units formed on the basis of professional lexicon are cross-analyzed. Differences and similarities in paremiological units of two peoples are demonstrated on the basis of a factual example
Keywords: paremiology; proverb; aphorism